Land Gradation Effect Analysis on Permeability and Ponding Time on Repeat Rain Frequency: Laboratory Study with Rainfall Simulator - Ilham Sudirman; Alamsyah (Newinera Publisher, 2020)
Analysis of Effect of Land Gradation on Permeability and Ponding Time in Frequency of Repeated Rain (Laboratory Studies with Rainfall Simulator) guided by Darwis Panguriseng and Mahmuddin. That soil permeability is the ability of soil to pass water or air. Soil permeability is usually measured in terms of the speed of water flowing in a certain time specified in units of cm/hour. Ponding time (tp) is the time difference between when it rains and the time when water begins to pool above ground level. The purpose of this study was to determine the effect of soil grading on permeability and inundation time with repeated frequency of rainfall with the same intensity on mixed soil types. This research method is a type of laboratory experimental research, using a rainfall simulator. The soil used in this study is mixed soil types. Furthermore, artificial rain is given with an intensity of I15, each intensity is used five times the frequency of rain and the inundation time readings and inundation height are carried out in the Rainfall Simulator experiment tank and for the permeability test, observation is done with the constant head test. The results showed the value of the permeability coefficient is inversely proportional to the increase in rainfall intensity and frequency of rain. Inundation height and final inundation time are directly proportional to increasing rainfall intensity and rainfall frequency.